Celebration: Ramadhan and staff birthday / Azlinda Mohamad Nor and Assoc. Prof. Dr. Mahmathi Karuppannan - Mohamad Nor, Azlinda; Karuppannan, Mahmathi (Faculty of Pharmacy, 2023)
On the 16th March 2023, the Recreation and Welfare Club of Faculty of Pharmacy, UiTM organised a program to celebrate Ramadhan and staff birthday. A total of 75 staff attended this program. This ceremony was held to prepare staff spiritually, mentally, and physically before welcoming the month of Ramadhan. The Surah Yasin recitation and tazkirah were given and led by Ustaz Haji Saiful Anuar Mohamed Sani from the Islamic Affairs Unit, UiTM Puncak Alam Campus.